Awareness of the character Nania in the short story Asma Nadia Entitled "Love of an Ordinary Man" Psychoanalysis by Carl Gustav Jung - Nurul Astry Ramadhany (Bulletin of Social Studies and Community Development, 2022)
Abstract: The ego is the center of all consciousness consisting of thoughts, memories and feelings.  This research is motivated by Carl Gustav Jung's Psychoanalysis on the short story by Asma Nadia.  This study uses a qualitative descriptive method and the object of this study is a short story entitled "Cinta Lelaki Biasa" by Asma Nadia.  Research data obtained from the results of reading and note-taking techniques.  The results of this study show the awareness of the character Nania in the short story which consists of aspects of the soul's function and also the attitude of the soul.   Keywords: psychoanalysis, asma nadia